Global Research Trends on Cognitive Neuroscience: A Scientometric Visualization - Hazarika, Rima; Sudhier, K G (Journal of Data Science, Informetrics, and Citation Studies)
Cognitive Neuroscience is a scientific field that studies the neural mechanisms underlying cognitive processes, such as perception, attention, memory, language, and decision-making. The present study explores the research productivity of cognitive neuroscience from 2013 to 2022 based on the Scopus database. 11,840 records were used to identify the most productive authors, preferred journals, co-occurrence of keywords, highly cited articles, funding agencies, countries' collaboration, and trend topics. Data analysis was performed using VOSviewer, R software, and MS Excel. The study indicates that most publications occurred in 2022, totaling 1,386 documents. Among the authors, Wang, Y. stands out as the most productive, contributing 1.42% of the publications. Frontiers in Psychology journal emerges as the most highly influential one. The study also reveals that the United States is the most collaborative nation, with 4,560 documents co-authored with other countries. The keyword analysis highlights "Neuroscience" as the most frequently occurring term, appearing 1,094 times. The National Institutes of Health (NIH) takes the lead as the top funding agency. This study holds great value for researchers and policymakers as it provides insights and information to develop strategies for further research and collaborations in the field.
Keywords: Scientometrics; Cognitive neuroscience; Collaborations; Co-Occurrence; Network; Vosviewer.